2011
DOI: 10.1007/s12223-011-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of McRAPD for typing and importance of biofilm production in a case of nosocomial ventriculoperitoneal shunt infection caused by Candida lusitaniae

Abstract: A case report of ventriculoperitoneal shunt infection caused by Candida lusitaniae in a 6-year-old patient with cerebral astrocytoma and obstructive hydrocephalus is presented briefly with emphasis on the course of antifungal treatment. Seven isolates recovered subsequently from the cerebrospinal fluid were studied retrospectively. To confirm identity, isolates were typed using pulsed-field gel electrophoresis and melting curve of random amplified polymorphic DNA (McRAPD). Further, the ability to form biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Candida spp. yeasts are generally known for considerable biofilm activity, which increases their virulent behaviour [ 61 , 62 ]. In this respect, the species Candida albicans is most often discussed in the literature [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Candida spp. yeasts are generally known for considerable biofilm activity, which increases their virulent behaviour [ 61 , 62 ]. In this respect, the species Candida albicans is most often discussed in the literature [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the principle of RAPD, its interlaboratory reproducibility will always be limited however although it can outdo conventional techniques in several aspects when optimized carefully 5 . It should also be noted, that because of the digital data obtained in melting analysis the McRAPD approach can be used for automated strain typing, as demonstrated by Hamal et al 26 . For those who do not want to spend too much time with optimization and who also resign on typing for epidemiological purposes, specific amplification targeting yeast ITS1 and ITS2 regions should be very useful 27 .…”
Section: Melting Analysis For Species Identification Purposesmentioning
confidence: 99%
“…McRAPD may be usefull mainly in such species where other molecular typing schemes are not easily available or are laborious, e.g. for serovars of Leptospira as demonstrated by Tulsiani et al 39 , or for less frequently occurring yeasts as demonstrated by Hamal et al 26 in the emerging pathogenic yeast C. lusitaniae. Comparison of McRAPD with MLST data in five Gram-negative bacterial species showed that McRAPD could be used to rapidly identify major clones of these species, including multidrug-resistant and particularly virulent clones 21 .…”
Section: Melting Analysis For Genotyping Purposesmentioning
confidence: 99%
“…to our previous experience. Melting analysis of RAPD, termed McRAPD, was first used by our group for purposes of yeast species identification 19 , but later proved to be useful for strain typing in several other settings 17,[20][21][22] . In this study, McRAPD provided excellent results that were in full accordance with the results of MLST, which is considered the gold standard for microbial typing.…”
Section: Maldi-tof Ms Strain Typingmentioning
confidence: 99%